THE USE OF ICT IN EFL CLASSROOMS: TEACHERS' READINESS, IMPLEMENTATION, AND CHALLENGES - Anggi Arigusman, - (2019)
The use of ICT requires teachers' readiness (Cahyani & Cahyono, 2017) because teachers are the key to whether or not the educational technology is used appropriately and effectively (Kumar, Rose, & Silva, 2008). Teachers' readiness includes knowledge, skills, and attitudes (Alazzam, Bakar, Hamzah, & Asimiran). Salehi and Salehi (2012) said that ICT to support teaching and learning provides big opportunities, but it is not free of problems. This research aims to explore the teachers' ICT readiness, implementation of ICT use, and challenges. A descriptive qualitative approach that involves questionnaire, interview, and observation as tools of data collection is used in the current study to achieve a comprehensive picture of the teachers' ICT readiness, implementation, and the challenges that the teachers encounter in implementing the use of ICT in EFL classroom. Thirty three English teachers were invited as questionnaire respondents. Two of them were observed and six of them were interviewed. Observation and interview participants were chosen purposively. The results appear that 86% of the teachers have already had good ICT readiness. Meanwhile, 14% of them still have low ICT readiness. Various challenges encountered by the teachers were identified in the interview. Lack of teachers' training and infrastructures was the main challenges found in this study. ;--- Penggunaan TIK membutuhkan kesiapan guru (Cahyani & Cahyono, 2017) karena guru adalah kunci apakah teknologi pendidikan digunakan secara tepat dan efektif atau tidak (Kumar, Rose, & Silva, 2008). Kesiapan guru mencakup dalam hal pengetahuan, keterampilan, dan sikap (Alazzam, Bakar, Hamzah, & Asimiran). Salehi dan Salehi (2012) mengatakan bahwa TIK yang digunakan untuk mendukung proses belajar mengajar membuka peluang yang besar, tetapi bukan berarti tanpa hambatan. Penelitian ini bertujuan untuk mengeksplorasi kesiapan para guru, implementasi penggunaan TIK, dan tantangan yang dihadapi. Pendekatan deskriptif kualitatif yang melibatkan kuesioner, wawancara, dan observasi sebagai alat pengumpulan data digunakan dalam penelitian ini untuk mendapat gambaran yang komprehensif tentang kesiapan, implementasi, dan tantangan guru dalam penerapan TIK di kelas EFL. Tiga puluh tiga guru bahasa Inggris dilibatkan sebagai responden kuesioner. Dua orang diantaranya diobservasi dan enam orang diwawancarai. Penentuan guru untuk observasi dan wawancara dipilih berdasarkan kriteria tertentu. Hasil penelitian menunjukan bahwa 86% guru sudah memiliki kesiapan yang baik dalam penggunaan TIK. Sementara, 14% di antaranya masih memiliki kesiapan yang rendah. Dalam wawancara beberapa hambatan yang dihadapi oleh para guru teridentifikasi. Kurangnya pelatihan dan infrastruktur menjadi tantangan utama yang ditemukan dalam penelitian ini.